2015
DOI: 10.1007/s00198-014-3015-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional variability in changes in the incidence of hip fracture in the Spanish population (2000–2012)

Abstract: Hip fractures continue to increase in absolute numbers, although if the rates are adjusted for age, a downward trend is seen in certain age groups. These findings have various origins, although in the absence of great changes in population structure, we believe that drug treatments for osteoporosis may play a role. There is variability in the change in incidence of hip fractures in different parts of the country. Further studies are required to be able to identify the causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…The crude incidence rate changed from 259.24 to 664.79 in 1997 to 325.30 and 766.37 in 2010, for men and women respectively (the study group consisted of patients 65+ years) [ 21 ]. The increasing trend of number of hip fractures was also confirmed by Foronda who analysed data in different regions of Spain [ 22 ]. In general, the number of hip fractures increases, but in some countries, the trend of incidence rate is decreasing [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 56%
“…The crude incidence rate changed from 259.24 to 664.79 in 1997 to 325.30 and 766.37 in 2010, for men and women respectively (the study group consisted of patients 65+ years) [ 21 ]. The increasing trend of number of hip fractures was also confirmed by Foronda who analysed data in different regions of Spain [ 22 ]. In general, the number of hip fractures increases, but in some countries, the trend of incidence rate is decreasing [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 56%
“…The strongest inequalities were observed in women between 65 and 79 years of age and increased during the BJD: while HF incidence persistently decreases in the affluent regions, the decrease in the medium regions was only for a short period of 3 years and, in the deprived regions, there was no decreasing period; besides, there are increasing trends starting first in 2006 in the deprived regions and later, in 2007, in the medium regions. Our results seem to show that HF reduction from 2000 to 2010 have mainly reached a restricted group: women aged 65–79 years in the affluent regions, the preferential target population for medication and treatment against osteoporosis and HF,31 32 while sustainable reduction seems to have failed for all the other men and women. All stable or increasing trends in 2000 (for all age groups and regional SES among women) turned to accentuate decreasing trends around 2002/2003, although such turning points were rarely observed for men.…”
Section: Discussionmentioning
confidence: 63%
“…First, although our cohort includes all patients after a hip fracture from Valencia, a region covering a population of 5 million inhabitants, this population represents approximately 11% of the overall Spanish population. Thus, results should be extrapolated with caution, especially given that studies have shown a considerable variability in hip fracture rates and osteoporotic treatment between different regions, even within the same country 21 , 22 . Second, we calculate secondary non-adherence with dispensing but no prescription data, so we cannot discern whether treatment interruption is instructed by clinicians or is due to patient’s non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the annual incidence of hip fracture is estimated at 72 and 28 per 10,000 women and men respectively, totalling roughly 40,000 hip fractures/year 6 . Moreover, the age and sex standardised rate of hip fracture per 10,000 inhabitants has remained relatively stable in the period 2000–2012 7 despite significant increments in osteoporotic medication prescription in the Spanish National Health System.…”
Section: Introductionmentioning
confidence: 99%